2009
DOI: 10.1111/j.1540-8183.2009.00427.x
|View full text |Cite
|
Sign up to set email alerts
|

A High Blood Pressure Predicts Bleeding Complications and a Longer Hospital Stay after Elective Coronary Angiography Using the Femoral Approach

Abstract: We conclude that systolic blood pressure and female gender are independent predictors of bleeding complications and that a high systolic blood pressure should be reduced before elective CA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 16 publications
0
3
0
2
Order By: Relevance
“…However, between 19 and 57% have no significant disease on angiography, depending on the population studied [3,4]. Although a generally safe procedure, complication rates for myocardial infarction (MI) and death are approximately 0.1% with bleeding complications quoted as high as 8.8% [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…However, between 19 and 57% have no significant disease on angiography, depending on the population studied [3,4]. Although a generally safe procedure, complication rates for myocardial infarction (MI) and death are approximately 0.1% with bleeding complications quoted as high as 8.8% [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Диагностика ИБС Золотым стандартом диагностики ИБС остается метод КАГ, однако ее стоимость относительно высока, и при ее проведении возможны различные осложнения, в т. ч. летальный исход (0,1-0,2%), нефатальный ИМ (0,1%), серьезные цереброваскулярные осложнения (0,1%), кровотечения (8,8%) [21][22][23]. Хорошо известно, что 19-57% больных ИБС в зависимости от популяционных особенностей [24] могут не иметь значимых ангиографических изменений коронарных артерий.…”
Section: цели проведения нпunclassified
“…Стоимость сцинтиграфии миокарда, однофотонной эмиссионной компьютерной томографии, магнитно-резонансной томографии и, особенно, позитронной эмиссионной томографии гораздо выше, чем ВЭМ [21]. Диагностическая точность радиоизотопного исследования, по одним публикациям сравнима с точностью стресс ЭхоКГ, по другим -это исследование обладает несколько более высокой чувствительностью [34].…”
Section: цели проведения нпunclassified
“…The relation between hypertension and blood viscosity has been documented in the published literature, as has the possible relationship between high blood pressure and spontaneous SEH. Recent studies in other fields have demonstrated the impact of perioperative hypertension on surgical outcomes, such as stroke, prolonged hospital stay, and postoperative bleeding complications. In contrast, the influence of postoperative hypertension on the development of symptomatic postoperative SEH is largely unknown.…”
Section: Introductionmentioning
confidence: 99%